Social change and community perceptions on change environment due to sand mining - Septriana, Fentinur Evida; Sari, Syahra Ariesta Fitria; Nugraha, Bayu; Putri, Kartika (Interaction, Community Engagement, and Social Environment, 2024)
Sand mining in Keningar village, which has been started since 1996, is still carried out by the community to date, even though the damage is already exist and severe. The community start to dredge the crop land to take the sand, then sell it. Sand mining activities are not only carried out by the residents of Keningar village, but also by another parties from outside the region. The change of land use from crop land into sand mining areas has many impact on various aspects of community life, both on social, economic and cultural aspects. The purposes of this study are to know the perspective of the community of Keningar village on sand mining activities that has been carried out to date, their effect for the environment, and social life patterns of the community of Keningar village. This study use qualitative method by describe all the information. The information was obtained from observations and unstructured interviews with several informants found at the site. The results of the study show that there is a social change in the community of Keningar village, caused by a paradigm shift from farmers to sand miners. The driving force for this phenomenon is economic factor, the demand for everyone needs are high. This paradigm shift has many effects not only on socioeconomic, but also for the environment. Massive exploitation of sand, gravel, and rocks cause the lost of fertile layers of soil and reduce groundwater reserves on community’s crop land. The sand mining can be controlled since the government applied mining license instrument. However, there is still illegal mining carried out between the landowners and mining entrepreneurs by simple agreement. In reality, the indigenous character of the community of Keningar village is farmers and charatcter of “nrimo ing pandum” which actually can be developed to an advance economy without damaging the environment, through the intervention of the government, academics, or other stakeholdes. And one of them can be solved through education.